Dexidation Symposium - The Total Oxygen Content of Plain Carbon Open-hearth Steel during Deoxidation and Teeming (With discussion) - Michael Tenenbaum; C. C. Brown (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1945)
Numerous investigatiolls have been carried out to determine the total oxygen present in the basic open-hearth bath and the results of these studies have clearly defined the factors controlling the bath oxidation during the period prior to deoxidation. On the other hand, very little is known concerning any changes in total oxygen content that may occur during deoxidation, tapping and teeming. The need for such additional data is continually becoming more apparent, since there is no strict technical basis for selecting any particular deoxidation practice. Many steels are made for the same purposes and to the same chemical analyses by widely differing practices. Apparently, each practice is satisfactory. However, it would be desirable to establish more definitely the effects and relative merits of the individual practices. Such information could be used to give a definite foundation for evaluating various types of deoxidation. In order to approach this problem, a study was made of the changes effected in the total oxygen content of several grades of steel by representative open-hearth deoxidation practices. To carry out such studies, it was necessary that a reliable testing procedure for determining the oxygen content of the steel bath and the ingot mold be established. Before entering on any extensive testing program, consideration was given to the available methods of obtaining steel samples and analyzing for oxygen. Testing Procedures It has been shown5-9 that in solidified steel oxygen may ekist in combination with iron, manganese, silicon, aluminum, titanium, chromium and carbon, depending upon the amount of these elements in the sample. In molten steel, however, there has been no direct distinction of the various oxides. Accordingly, the total active oxygen in the molten steel bath is designated by the symbol 0. During deoxidation, various oxides may be present either in solution in the molten steel or as solid or liquid inclusions. Any sample taken from the molten steel for oxygen analysis will include both the dissolved and the mechanically included oxygen. Similarly, samples of the solid steel product will also include the two forms of Oxygen' Methods of Samplirzg the Molten Steel Bath In order to obtain a true oxygen analysis from liquid steel, this element must be completely retained in the solidified sample. Several methods have been proposed whereby this stabilization can be effected. As early as 1915, Kichlinelo proposed a method for testing molten steel, in which the oxygen combined with some added aluminum. The concentration of the resultant aluminum oxide was determined by chemical analysis. This method was